2015
DOI: 10.1016/j.tcb.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modifications of tubulin: pathways to functional diversity of microtubules

Abstract: Tubulin and microtubules are subject to a remarkable number of posttranslational modifications. Understanding the roles these modifications play in determining functions and properties of microtubules has presented a major challenge that is only now being met. Many of these modifications are found concurrently, leading to considerable diversity in cellular microtubules, which varies with development, differentiation, cell compartment and cell cycle. We now know that posttranslational modifications of tubulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
305
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(320 citation statements)
references
References 135 publications
12
305
0
1
Order By: Relevance
“…Acetylation is a reversible posttranslational modification that plays a fundamental role in the epigenetic regulation of gene expression 34. Interestingly, αTAT1 (also known as MEC‐17) is a specific acyltransferase that promotes α‐tubulin acetylation on lysine 40 (K40), and many studies have verified that elevated levels of acetylated α‐tubulin are a marker of stable microtubules 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation is a reversible posttranslational modification that plays a fundamental role in the epigenetic regulation of gene expression 34. Interestingly, αTAT1 (also known as MEC‐17) is a specific acyltransferase that promotes α‐tubulin acetylation on lysine 40 (K40), and many studies have verified that elevated levels of acetylated α‐tubulin are a marker of stable microtubules 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to specific microtubule-associated proteins, posttranslational modifications of tubulin are emerging as a significant mechanism that controls various microtubule functions, such as the recruitment of +TIPs and microtubule motors (Akhmanova and Steinmetz, 2008;Etienne-Manneville, 2013;Janke and Bulinski, 2011;Song and Brady, 2015). An interesting example is tubulin acetylation, a modification that is introduced by α-tubulin Nacetyltransferase 1 (ATAT1, hereafter referred to as αTAT1) and is removed by histone deacetylase 6 (HDAC6) (Song and Brady, 2015).…”
Section: Microtubule-associated Proteins In 3d Cell Migrationspecificmentioning
confidence: 99%
“…Importantly, we show that ALC partially prevents METH-induced deacetylation, protecting the endothelial cells and consequently preserving the BBB function. Cytoskeleton microtubules are regulated by several types of conserved posttranslational modifications (Song and Brady, 2014). Although the biological meaning of such mechanisms is still poorly understood, it was reported that tubulin acetylation increases its stability and half-life, rendering microtubules more resistant to druginduced depolymerization and disassembly (Matsuyama et al, 2002;Szyk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%